Unveiling the distinctive qualities of Malaysian and Thai rice - Shamsudin, Rosnah; Muchlisyiyah, Jhauharotul; Sathongpan, Parichat; Varith, Jaturapatr; Hamzah, Muhammad Hazwan (Mustansiriyah University College of Engineering, 2025)
This work compared the chemical and thermal properties of Malaysian and Thai rice cultivars. Malaysian rice was obtained from Terengganu, Malaysia, while Thai rice samples were Khao Hom Mali from Royal Umbrella Thailand. The paired-T statistic was employed to examine the chemical and thermal parameters. While there were no statistically significant differences in the amylose, moisture, and fat composition between the two samples (p>0.05), there were notable disparities in the protein, ash, carbohydrate, and fiber composition (p<0.05). Malaysian rice cultivars exhibited higher levels of protein (7.8%), ash (53%), and carbohydrate content (25.88%), whereas Thai rice possessed a fiber content that was five times greater. Regarding thermal characteristics, Malaysian rice exhibited higher values for onset (21.5%), conclusion (6.5%), and peak (8.7%), although Thai rice had a gelatinization range that was three times higher. These findings indicate that Malaysian rice yields firmer textures, rendering it appropriate for certain grain cuisines where separated grain is required. In contrast, Thai rice's softer, more adaptable texture might be suited to different culinary applications, improving consumer tastes and industrial utilization.